Controllability robustness of heat exchanger network based on complex network theory. Issue 6 (4th October 2021) - Wang, Zheng; Dong, Ran; Dong, Yunqing; Li, Huapeng; Liu, Ruijie; Hu, Yiyi; Jia, Xiaoping; Wang, Fang
Abstract: With the rapid development of process industry, the heat exchanger network is becoming larger and more complicated. The heat exchanger network will inevitably be subject to internal and external interference, resulting in cascading failures, which reduces the controllability of the heat exchanger network and affects normal operation. A controllability robustness analysis method is proposed based on the complex network theory, to enhance the ability of the heat exchanger network to operate normally under external interference. First, combined with the interference transfer law of the heat exchanger network, a weighted directed complex network model of the heat exchanger network is constructed. Then, based on the controllability robustness analysis method of the minimum driver node, the controllability robustness of the heat exchanger network under four different attack modes is analyzed and compared. The comparative analysis of examples proves that the method takes into account the global controllability, accurately determines the attack modes and attack targets that have a greater impact on the controllability robustness of the heat exchanger network, reduces the computational complexity, and provides theoretical basis for improving the controllability robustness of the heat exchanger network and maintaining the normal operation of the heat exchanger network.